The Atelier in Newly Qualified Teacher Training Curriculum - Mangione, Giuseppina Rita (Formazione & insegnamento, 2017)
The trend started in cooperation with Professional Ateliers to include laboratory activities in the training curricula for teachers finds a recall in the Neoassunti training model. They are “adult” workshops proposing a training model based on problems and not on exercises, where the link between theories and practices is strengthened through relevant examples of learning situations. In order to have an insight into the effectiveness of the laboratory included in the curriculum of the training course dedicated to the Induction period and to identify the aspects to be improved, we conducted a reseach organized in a massive collection phase (involving 84,000 teachers and 117 principals) and in a case study in the Campania Region (involving 83 laboratory experts, 7 principals and the responsible of the USR. The research, adopting both quantitative and qualitative analysis tools, identifies reorganization elements for a professional lab, some of which are already contained in the most recent ministerial circulars, thus contributing to a evidence- based policy process.